The Influence of Store Atmosphere, Service Quality and Consumer Satisfaction on Consumer Loyalty in Chotaffeein Coffee and Roastery Kotamobagu, North Sulawesi - Mokoginta, Mia Istiana; Soegoto, Agus Supandi; Pandowo, Merinda H. Ch. (Abdurrauf Science and Society, 2025)
One way to increase and retain consumers at Chotaffeein Coffee and Roastery is to have consumer loyalty. Service quality is the main factor that influences consumer loyalty because satisfied consumers will recommend it to other consumers. Apart from that, Chotaffeein Coffee and Roastery also provides a good store atmosphere, which is one strategy for pursuing consumer loyalty. This research aims to determine the influence of Store Atmosphere, Service Quality and Consumer Satisfaction on Consumer Loyalty at Chotaffeein Coffee and Roastery Kotamobagu, North Sulawesi. This research used multiple linear regression analysis with a sample size of 96 respondents at Chotaffeein Coffee and Roastery Kotamobagu, North Sulawesi. The results of this research show that Store Atmosphere, Service Quality, and Consumer Satisfaction simultaneously influence Consumer Loyalty at Chotaffeein Coffee and Roastery Kotamobagu, North Sulawesi. Store Atmosphere influences Consumer Loyalty at Chotaffeein Coffee and Roastery Kotamobagu, North Sulawesi. Service Quality influences Consumer Loyalty at Chotaffeein Coffee and Roastery Kotamobagu, North Sulawesi, and Consumer Satisfaction influences Consumer Loyalty at Chotaffeein Coffee and Roastery Kotamobagu, North Sulawesi. The marketing management at Chotaffeein Coffee and Roastery Kotamobagu, North Sulawesi should pay more special attention to the aspects of consumer satisfaction, service quality and a comfortable shop atmosphere as the main priority in serving consumers by increasing the role of management